Strengthening Consumer Brand Relationships through Consumer Engagement: Online Brand Communities in Landscape of Social Media - Muhammad Sheeraz; Mariam Tanweer; Kanwal Iqbal Khan; Shahid Mahmood (Pakistan Journal of Social Sciences (PJSS), 2017)
The study advances conceptualization and dimensionality of consumer engagement and validate antecedents and outcomes in the context of social media. The data collected from active members of online brand communities, unveiled that consumers engage with brands and other consumers with brand communities. The study conducted exploratory factor analysis, confirmatory factor analysis and hierarchical regression modelling to validate construct and test proposed hypotheses. Findings of the study exhibit that brand satisfaction, brand identification yield significant relationship with consumer engagement while brand trust turns out to be insignificant. Furthermore, consumer engagement significantly mediates the relationship between brand identification, brand satisfaction and brand loyalty. The study asserts that parsimonious conceptualization of consumer engagement consists of three dimensions: cognitive, affective and behavioral. Contributions of the study are two folds; first, endorse consumer engagement conceptualization and secondly, answer to call for empirical testing of Online Brand Community Engagement Framework.
Keywords: M3; M31; M30; M37; 330; Consumer Engagement; Online Brand Community; Brand Identification; Brand Satisfaction; Brand Loyalty